THE XBRL, NEW LANGUAGUE OF COMMUNICATION OF PUBLIC ACCOUNTANTS OF PERU - Pastor Carrasco, Carlos Alberto (2009)
The initials XBRL means: eXpansible Business Reporting Language. It is a language more than the family of XML2 that is transforming into a standard of the media of information among the companies in Internet. It is a language for the electronic communication of financial data and of businesses that it is revolutionizing the way of informing from all over the world in the companies. It provides important benefits in the preparation, analysis and communication of managerial information. He offers saving of costs, bigger efficiency and better precision and reliability to all those implied in the supply or in the use of the financial data. The countable professional is very aware of the necessity of systematizing the exchange of financial information as a consequence of her many years of experience with countable automated systems. In little more than 11 years this simple idea has been able to attract the interest and the back of an entire community of individuals and public and private organizations that represent a great number of countries, coordinated in International XBRL, an international organization without spirit of lucre that leads the development and maintenance of standard XBRL and to the one that they belong more than 550 institutions. The topic of standard XBRL is investigated with the purpose of fomenting its diffusion and future use on the part of the public accountants of the country in order to facilitate the exchange of financial information between the companies and the government. Also, it looks for to motivate among the students of the countable profession the development of investigation projects that they allow the creation of the necessary taxonomy for their use.